Characterizing the lethal and sub‐lethal effects of genetically modified soybean expressing Cry1A.105, Cry2Ab2, and Cry1Ac insecticidal proteins against Spodoptera species (Lepidoptera: Noctuidae) in Brazil. Issue 2 (21st October 2022) - Barcellos, Giovani A; Hanich, Manoela R; Pretto, Venicius E; Weschenfelder, Marlon A G; Horikoshi, Renato J; Dourado, Patrick M; Ovejero, Ramiro F L; Berger, Geraldo U; Martinelli, Samuel; Head, Graham P; Bernardi, Oderlei
Abstract: BACKGROUND: MON 87701 × MON 89788 × MON 87751 × MON 87708 soybean, that expresses Cry1A.105, Cry2Ab2, and Cry1Ac insecticidal proteins and confers tolerance to glyphosate and dicamba, is a potential tool for managing Spodoptera species in soybean fields in Brazil. In this study, we characterized the lethal and sub‐lethal effects of Cry1A.105/Cry2Ab2/Cry1Ac soybean against Spodoptera species and genotypes of Spodoptera frugiperda resistant and susceptible to Cry1 and Cry2 proteins. These evaluations were also conducted with MON 87701 × MON 89788 soybean, which expresses Cry1Ac protein. RESULTS: Cry1A.105/Cry2Ab2/Cry1Ac soybean caused high lethality in neonates of Spodoptera cosmioides and Spodoptera albula . However, it showed low lethality in S. frugiperda genotypes homozygous for resistance to Cry1 and Cry2 proteins but reduced their population growth potential. No relevant lethal effects of Cry1Ac soybean were detected in the Spodoptera species and genotypes evaluated. Spodoptera frugiperda genotypes heterozygous for Cry1 and Cry2 resistance were controlled by Cry1A.105/Cry2Ab2/Cry1Ac soybean, with no insects developing into adults. This Bt soybean also caused intermediate mortality of neonates of Spodoptera eridania (60%–83%) but no surviving larvae developed to adulthood, resulting in population suppression. CONCLUSIONS: Cry1A.105/Cry2Ab2/Cry1Ac soybean caused high mortality of S. cosmioides, S. albula, and S. frugiperda genotypes susceptible to Cry1 and Cry2 and heterozygous for Cry1 and Cry2 resistance. This Bt soybean also suppressed population growth of S. eridania but had minimal impact on S. frugiperda homozygous for resistance to Cry1 and Cry2 proteins. Cry1Ac soybean had minimal impact on all Spodoptera species and genotypes evaluated. © 2022 Society of Chemical Industry. Abstract : Species of genus Spodoptera are commonly found in soybean fields in Brazil. In this research were reported the lethal and sub‐lethal effects of Cry1A.105/Cry2Ab2/Cry1Ac soybean against Spodoptera species and S. frugiperda genotypes that were susceptible, heterozygous, and homozygous‐resistant to Cry1 and Cry2 proteins.